Mycorrhizae: A Rhizolive Symbiotic Fungi in Organic Agriculture - , G. Gayathry; , K. Natarajan; , T. Jayalakshmi; , R. Vinu Radha; , M.P. Sugumaran; , R. Sunitha; , K. Kumutha (Archives of Current Research International, 2024)
Mycorrhizae, a symbiotic association between fungal hyphae and plant roots, play a crucial role in achieving sustainable development goals in natural farming by enhancing soil structure, nutrient uptake, and plant growth. Arbuscular Mycorrhizae (AM) and Ectomycorrhizae are often encouraged in no-tillage systems and conservation agriculture. Mycorrhizal fungi, particularly within the rhizolive consortium, are shown to improve soil fertility, water retention, heavy metal degradation, and disease resistance. They assist in nutrient cycling, especially phosphorus, and contribute to soil aggregation through the secretion of Glomalin-Related Soil Proteins (GRSP). The use of AM fungi in pest and disease management, land rehabilitation, and bioremediation is highlighted, emphasizing their potential in sustainable agriculture. The paper also outlines methods for the mass production of Arbuscular Mycorrhiza Fungi as biofertilizers, including soil-less culture, carrier-based inoculum, and hairy root culture techniques. Certain agronomic practices and modifications in the existing land management practices by multiple cropping systems rather than mono-cropping to deliberately improve the resource use efficiency and soil organic carbon dynamics through this symbiotic relationship in enhancing soil health, plant productivity, and ecological balance in farming systems.